Dynamic Pricing for Local Energy Management : Towards a Better Integration of Local Production. Issue 1 (July 2017) - Muller, A.; Bourdais, R.
Abstract: Dynamic Pricing or TOU (Time Of Use) pricing enables grid managers to perform non invasive energy management where consumers keep full control of their energy consumption. The main contribution of this work is to propose a distributed optimization structure to have a better integration of local production. More precisely, instead of having a centralized solution, whose optimization is hard to solve and does not preserve the privacy of the consumers, a distributed solution is proposed, using price inducements. This price is deduced iteratively from an adaptation of augmented Lagrangian technique. The performances of the proposed strategy is compared with the centralized control and a "do nothing" approach.